Upregulation of heme oxygenase-1 mediates the anti-inflammatory activity of casein glycomacropeptide (GMP) hydrolysates in LPS-stimulated macrophages. Issue 7 (21st June 2017) - Li, Tiange; Cheng, Xue; Du, Min; Chen, Bin; Mao, Xueying
Abstract : Recently, we have shown that casein glycomacropeptide hydrolysates (GHP) exhibit both anti-inflammatory and anti-oxidative activities in vitro . Abstract : Recently, we have shown that casein glycomacropeptide hydrolysates (GHP) exhibit both anti-inflammatory and anti-oxidative activities in vitro . However, whether heme oxygenase-1 (HO-1) is involved in the cytoprotective effect of GHP against the inflammatory status remains unclear. Therefore, we hypothesized that HO-1 is a potential target of GHP, which mediates its anti-inflammatory effect. Here, GHP inhibited the intracellular reactive oxygen species (ROS) accumulation and NADPH oxidase 2 (NOX2) expression and enhanced reduced glutathione (GSH) levels in LPS-stimulated RAW264.7 macrophages. GHP also suppressed the expression of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6) and inducible nitric oxide synthase (iNOS) stimulated by lipopolysaccharide (LPS). However, zinc(ii )-protoporphyrin IX (ZnPPIX), a selective inhibitor of HO-1, restored the GHP-mediated suppression of ROS production and NOX2, TNF-α, IL-1β, IL-6 and iNOS expression. GHP treatment inhibited the LPS-induced nuclear transcription factor kappa-B (NF-κB) translocation, which was markedly reversed by ZnPPIX. Furthermore, GHP induced the phosphorylation of extracellular signal-regulated kinase 1/2 (ERK1/2), Akt and p38. Pharmacological inhibition of Akt, ERK1/2, and p38 abrogated GHP-induced nuclear localization of NF-E2-related factor-2 (Nrf2) and the expression of HO-1. In summary, GHP inhibits the LPS-induced inflammatory status through upregulating HO-1 expression via PI3K/Akt, ERK1/2 and p38 signaling pathways in RAW264.7 macrophages.